Best Answer

4x - 10 = -4x + 22

+4x+10=+4x +10

8x = 32

x = 4

User Avatar

Wiki User

โˆ™ 2012-09-09 16:57:27
This answer is:
User Avatar
Study guides


20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

See all cards
846 Reviews

Add your answer:

Earn +20 pts
Q: How do you work out the equation 4x-10 equals -4x plus 22?
Write your answer...
Still have questions?
magnify glass
Continue Learning about Algebra

What is the correct first step for solving the equation 5x plus 3 equals 8?

5x+3=8 is a simple equation, and I can tell you off the top of my head the answer is 1. Here's how to work it: 5x+3=8 5x+3(-3)=8(-3) 5x=5 5x(/5)=5(/5) x=1

What is the radix of the numbersif the solution to the quadratic equation x2-10x 31 is x equals 5 and x equals 8?

Unfortunately, limitations of the browser used by means that we cannot see most symbols. There is no equality symbol in the equation and if one is inserted before the 31, the solutions do not work.One way to make the question work is to rewrite the quadratic equation asx2 - 10x + 31 = 0 which requires adding 3 characters (all in bold).It is therefore impossible to be certain about the answer to your question. If that is the case, the radix is 13. Otherwise, please resubmit your question spelling out the symbols as "plus", "minus", "equals", "squared".

What is the answer to 3x plus 2y - 5 equals 0 x equals y plus 10?

3x+2y-5=0 3x+2y=5 Im lost im only 12 work out the rest hope i helped

In the equation 4x-7 equals 13 solve for x?

5 it is 5 because 13 + 7 = 20 20 divided by 4 is 5 to find out the answer, work through the equation backwards and use the opposite operations.

What is 3x plus 6y equals 42 and -7x plus 8y equals -109 please use elimination and show work Thanks?

4(3x+6y = 42) 3(-7x+8y = -109) Multiply all terms in the top equation by 4 and in the bottom by 3: 12x+24y = 168 -21x+24y = -327 Subtract the bottom equation from the top remembering that a minus from a minus is equal to a plus: 33x = 495 Divide both sides by 33: x = 15 Substitute the value of x into the original equations to find the value of y: Therefore: x = 15 and y = -1/2

Related questions

How do you work out 12 plus 4x10?

12 + 4*10 = 12+40 = 52

How can you show your work to solving the equation of 5x-2y equals -10 3x plus 6y equals 66?

There are 2 unknowns

What is three minus negative nine with the work?

3-(-9) Considering a negative plus a negative equals a positive your equation can be rewritten as 3+9 Which equals 12

What does 15--13 equal 15 --13 equals 28 because a minus and a minus equals a plus so the equation is actually 15 plus 13 equals 28 p.s. i am only 10 years old?

Good work ! Did you have a question you wanted to ask ?

What are the solutions to the simultaneous equation of 3x plus 2y equals 5x plus 2y equals 14 showing work?

If: 3x+2y = 5x+2y = 14 Then: 3x+2y = 14 and 5x+2y =14 Subtract the 1st equation from the 2nd equation: 2x = 0 Therefore by substitution the solutions are: x = 0 and y = 7

Equals force applied times distance moved?

This is the equation for "work."

What equation defines work?

W = F * d Work equals Force times distance

What are the solutions to the simultaneous equations of 3x -y equals 5 and 2x2 plus y2 equals 129?

The solutions work out as: x = 52/11, y = 101/11 and x = -2, y = -11

How do you work out y equals x?

It depends on the rest of the equation and the form it takes.

2x-3y equals -2 4x plus y equals 24 use substitution method and work the system of equation?

how do you use the substitution method for this problem 2x-3y=-2 4x+y=24

Could you work this out 6.100 plus 4.10 plus 7 equals?

yes I can = 17.2

What is the square root of x-4 plus 6 equals x?

x-4+6=x This is equation is false because if you work it out you get 2=0 and two does not equal zero. And you cant take the sqrt of a false equation.

People also asked